ответ: -11
Объяснение:
y'=-7-7V2(-sinx)=-7+7V2sinx, -7+7V2sinx=0, поделим на 7,
V2 sinx=1, sinx=V2/2, x=p/4, теперь надо подставлять
значения 0, р/4, р/2 в функцию,
y(0)=3+7p/4-7*0-7V2cos0=3+7p/4 -7V2 *1
y(p/4)=3+7p/4-7*p/4 -7V2*cos (p/4)=3-7V2 *V2 /2=3-14=-11
y(p/2)= на ЕГЭ ответ идет без Пi
ответ: -11
Объяснение:
y'=-7-7V2(-sinx)=-7+7V2sinx, -7+7V2sinx=0, поделим на 7,
V2 sinx=1, sinx=V2/2, x=p/4, теперь надо подставлять
значения 0, р/4, р/2 в функцию,
y(0)=3+7p/4-7*0-7V2cos0=3+7p/4 -7V2 *1
y(p/4)=3+7p/4-7*p/4 -7V2*cos (p/4)=3-7V2 *V2 /2=3-14=-11
y(p/2)= на ЕГЭ ответ идет без Пi